2005
DOI: 10.1016/j.yjmcc.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Young MLP deficient mice show diastolic dysfunction before the onset of dilated cardiomyopathy

Abstract: Targeted deletion of cytoskeletal muscle LIM protein (MLP) in mice consistently leads to dilated cardiomyopathy (DCM) after one or more months. However, next to nothing is known at present about the mechanisms of this process. We investigated whether diastolic performance including passive mechanics and systolic behavior are altered in 2-week-old MLP knockout (MLPKO) mice, in which heart size, fractional shortening and ejection fraction are still normal. Right ventricular trabeculae were isolated from 2-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…As reported previously, 23,[35][36][37] MLPKO hearts show an increase in passive stiffness. Normalization of the LVEDP in the DKO hearts indicated that the impaired filling in the MLPKO hearts was rectified in the absence of the AT1a receptor (Table 2).…”
Section: Gene Expressions In Mlpko and Dko Heartssupporting
confidence: 85%
“…As reported previously, 23,[35][36][37] MLPKO hearts show an increase in passive stiffness. Normalization of the LVEDP in the DKO hearts indicated that the impaired filling in the MLPKO hearts was rectified in the absence of the AT1a receptor (Table 2).…”
Section: Gene Expressions In Mlpko and Dko Heartssupporting
confidence: 85%
“…This is consistent with studies in titin N2B-deficient mice, which demonstrate that the N2B region of titin affects diastolic but not systolic function of the heart (31). Multiple mechanisms of titin-based stretch sensing and signaling pathways have been proposed within the central I band (5,32). However, our studies demonstrate an in vivo role for the titin N2B binding partner, FHL1, in diastolic function and biomechanical stress responses involved in pressure overload-induced hypertrophy.…”
Section: Discussionmentioning
confidence: 55%
“…LVIDd, LV internal dimension at end-diastole. *P < 0.05; **P < 0.01. results of studies in MLP- and titin N2B-deficient mice, in which the reduced passive tension and basal cardiac muscle defects were likely due to shortened sarcomere slack lengths (4,31,32). Extracellular collagen is one of the major contributors to myocardial diastolic tension at longer sarcomere lengths (43).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the phenotype of young MLP -/-mice, it has been proposed that the progression to heart failure in the MLP deficiency model may be driven by diastolic dysfunction and abnormal passive properties rather than systolic dysfunction (Lorenzen-Schmidt et al, 2005). MLP interacts with Tcap, and mutations in the Tcap binding region of MLP have been found in a subset of patients with dilated cardiomyopathy (Knöll et al, 2002).…”
Section: Candidate Partners Of Z-disc-associated Proteins In the Strementioning
confidence: 99%